The Lord’s Supper: an analysis of the problem occurred in Corinth - do Espírito Santo, Magno Lessa (Vox Scripturae - Revista Teológica Internacional, 2017)
The present work aims to find out the reasons which led into a conflict during the right Lord’s supper moment in the Christian community so called Corinth. Like that we all start from the following resentment: what was the problem occurred in that moment? In order to get through with an answer for that issue is necessary in first place, to get a good information for a better analysis, in Corinth, aiming the social layers side present, in special in the boss network. Following up, the Corinth situation should be well delimited, in the “Lord’s supper” celebration it’s concerned, in the Christian community of Corinth, pushing up the need of communion in the banquet and the equality the members take, just because, they au part of unique Christ’s Body. In the end, should be showed that from the participants were asked for the exclusive in the share of the Lord’s table, besides being known as members, also get the “border” well cleared to get protected from a sort of cult association. Stand the search of other as: Meeks, Dunn, Crossan and Reed Theissen, among other important well regarded scholars who spent a long time on the matter, the banquet can be noted, in there celebrated, offer to the rich people firstly - to get over the poor, as those are used to get fed, before the other - as many of them work, up to a later time and they were eating all what that had left behind.
Keywords: Corinth; Christian community; Lord’s supper